A literacy‐sensitive approach to improving antibiotic understanding in a community‐based setting. (18th January 2017) - David, Crystal M.; O'Neal, Katherine S.; Miller, Michael J.; Johnson, Jeremy L.; Lloyd, Ann E.
Abstract: Objective: Antibiotic misuse contributes to antibiotic‐resistant bacterial infections. Patient and prescriber knowledge and behaviors influence antibiotic use. Past research has focused on describing and influencing prescriber behavior with less attention to the patient role in antibiotic use. This study seeks to: (1) develop and deploy a program to enhance patient knowledge about antibiotic use; (2) evaluate whether providing patient education is associated with improvements in antibiotic knowledge in a community‐based sample; and (3) explore whether health literacy may be associated with knowledge of appropriate antibiotic use. Method: This study developed, deployed, and evaluated whether community‐based educational seminars enhance patient knowledge about antibiotic use. Key findings: Twenty‐eight participants from five locations completed the seminar. The antibiotic knowledge index score significantly increased by 2.0 points on the 14 point knowledge index from 10.95 (±2.88) to 12.95 (±1.72) ( P = 0.0011) for the 19 participants completing both the pre and post‐test. Conclusion: A community‐based educational seminar on appropriate antibiotic use can effectively increase patient understanding of their role in antibiotic stewardship and combat the inappropriate use of antibiotics.